Laboratory Tests of Sampling Techniques. - Meier, Norman C.; Burke, Cletus J. (Public Opinion Quarterly)
This article points out certain limitations to quota sampling and area sampling in opinion polling. Each of the two general types of sampling techniques used in large-scale surveys, briefly referred to as quota methods and area methods, has adherents who claim superiority for it over the other. Area methods require that interviews be made only in specified, circumscribed areas and that within these areas every pertinent individual, or a strictly random subsampling of such individuals, be interviewed. The quota method comes out better on the point for point comparison. The results on home-ownership indicate the possibility of unwitting bias in the quota samples. On income alone, the quota method is better than simple random sampling. There is some evidence that neither method is as efficient as simple random sampling for the composite results on all three variables. This study shows that, in all probability, the differences between the results obtained by the two methods are not so great that a clear-cut superiority for one or the other can be easily demonstrated.